Students’ Perception of the International Class Program (ICP) in Supporting Speaking Skills at Math Education Study Program UNP - Srg, Hadi Saputra; Hanifa, Rizaldy (Journal of English Language Teaching, 2025)
English-speaking skills are essential for students to succeed in academic and professional settings. Universitas Negeri Padang offers the International Class Program (ICP) to enhance students' English proficiency, including speaking skills, for some majors, such as Mathematics Education. This study aims to find out students' perceptions of the ICP in supporting their speaking skills. Using a qualitative case study approach, data were collected through semi-structured interviews with ten students from the 2021 Mathematics ICP. The results show that students perceived improvements in vocabulary, grammar, pronunciation, fluency, and comprehension. They reported increased confidence and a reduction in speaking anxiety. Supportive teaching methods, consistent use of English by lecturers, and active classroom interaction contributed to these improvements.